ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI PADA DINAS PENDAPATAN, PENGELOLAAN KEUANGAN DAN ASET (DPPKA) KOTA BENGKULU - Dwi Linda Yuliarti; Ida Anggriani (UNIVED Press, 2014)
Dwi Linda Yuliarti, Ida Anggriani; An Analysis Of Factors That Influence Employee Performance In Department Of Revenue , Finance And Asset Management Of Bengkulu City. The purpose of the study to determine the most dominant factor affecting the performance of employees in Department of Revenue , Finance and Asset Management (DPPKA ) Bengkulu City . Data collection method used in the study was a questionnaire method , while the method of analysis using a Likert scale , and the rating scale . By the five factors that affect the performance of employees in Department of Revenue , Finance and Asset Management ( DPPKA ) Bengkulu city , four factors are personal factors, team factors, systems factors, and contextual factors got the perception of respondents agreed criteria, means that four factors affect the performance of employees . While one factor got the strongly agree perception is leadership factors, that greatly affect employee performance leader . The most dominant factor affecting the performance of employees inDepartment of Revenue , Finance and Asset Management (DPPKA) Bengkulu is leadership factors , because they have an important role in nurturing , supportive.